THE ROLE OF DA'I AS GUARDIAN OF THE INTEGRITY OF THE REPUBLIC OF INDONESIA - Zaenuri, Lalu Ahmad (KOMUNITAS, 2023)
A preacher as the subject of preaching activities plays a crucial role in determining the direction of the influence of their preaching. However, it is regrettable to observe the reality of preaching conducted by some preachers today, which is filled with condemnation, judgment, and provocation. The duty of a preacher is to convey (tabligh), not to judge or provoke. This phenomenon can trigger actions that may cause division within the Indonesian nation. In fact, several social conflicts have occurred in Indonesia due to judgments and provocations from certain parties. In Indonesia, there have been instances of public property destruction deemed as places of vice by preaching activists. The case of a family in Surabaya on May 13, 2018, conducting a suicide bombing to destroy places of worship for non-Muslims and the provocation of religious figures towards the community during each election event serves as an example.